Rennäringens kulturella värden - Egbäck, Samuel (2009)
The Swedish reindeer husbandry has had economic difficulties for some years. Due to this, and the fact that the reindeer husbandry plays an important role in Sámi culture, the Swedish state has chosen to support the industry. If these grants where to be withdrawn, the reindeer husbandry as well as the Sámi culture would decrease, which would cause welfare losses for the people living in Sweden. The aim of this study was to elicit what the Swedes are willing to pay to maintain the amount of reindeer husbandry and Sámi culture. By using Contingent Valuation and a survey the willingness to pay was estimated. During October 2008 the survey was sent to a random sample of 1200 Swedes between 18 and 75 years of age. Of these 50 % answered. To further understand the people’s preferences a study of the non-respondents was conducted. The calculation used two parametric and two non-parametric estimators, resulted in a median willingness to pay between 100-367 SEK annually. These results showed a notable difference compared to the grants from the state, indicating that the willingness to pay was clearly higher. The results also said contradictively that the Swedes are satisfied with the extent of today’s reindeer herding.